Phospho flow cytometry of PBMCs in psoriasis. (24th August 2018) - Aarebrot, A.K.; Solberg, S.M.; Davies, R.; Bader, L.I.; Holmes, T.D.; Gavasso, S.; Bryceson, Y.T.; Jonsson, R.; Sandvik, L.F.; Appel, S.
Summary: Psoriasis is a chronic inflammatory skin disease, which affects approximately 2% of the population. Severe psoriasis is often treated by inhibition of a molecule which plays a role in psoriasis, called tumour necrosis factor, by the drug infliximab. Recently, a much cheaper variant (a biosimilar) of infliximab, CT‐P13, produced by a different company, has been introduced. This study from the University of Bergen, Norway, aimed to compare activation of white blood cells from infliximab‐treated patients and healthy controls, and to investigate if switching from original infliximab to biosimilar CT‐P13 affected disease activity and activation of white blood cells (which is linked to psoriasis). Blood samples were collected at three time points from 25 patients who had been diagnosed with severe psoriasis. When taking the first blood sample, all patients were already treated with original infliximab. Then, patients either continued this treatment or switched to CT‐P13. 19 age‐, gender‐ and BMI matched healthy controls were also included. The activation level of selected molecules inside the cells was measured and was found to be higher in psoriasis patients than in healthy controls. This was despite the fact that the psoriasis patients at that time had little skin rash. However, the activation inside the cells declined during continued treatment. No clear differences were detected between the patient groups (original infliximab or CT‐P13) after 12 months. These findings suggest that people with severe psoriasis have on‐going inflammation in the blood, despite having resolved the skin rash by treatment with infliximab. This may be associated with an increased risk of cardiovascular disease. This study also supports that switching from original infliximab to CT‐P13 is safe. Abstract : Linked Article:  Aarebrot et al. Br J Dermatol 2018;179 :371–380